11. THE STATUS OF SOCIAL WORK ACTIVITIES AT SOME HOSPITALS IN HANOI 2024 (Tạp chí Y học Cộng đồng, 2024)
Objectives: Describe the status of social work activities at some hospitals in Hanoi 2024.Methods: A cross-sectional descriptive study on medical staff working at several hospitals in Hanoi. Data were collected through a toolkit developed based on Circular No. 43/2015/ TT-BYT dated November 26, 2015 of the Minister of Health, regulated the tasks and forms of organization of social work in hospitals.Result: Health workers performed the most activities such as reception (63.6%), communication guidance (44.6%), and hospitalization (43.8%), while home treatment consultation had the lowest rate (22.3%). Service connection was highest for diagnosis and financial support (47.1%), while emergency support had the lowest rate (13.2%). Popular activities included support for discharge procedures (43.8%) and follow-up visits (43%), while the reception rate was lowest (23.1%). At the three hospitals National Cancer, Bach Mai, and National Children's Hospital, the rate of staff who had participated in social work training programs was 39.7%, while 60.3% had not participated. In addition, 64.5% of staff wanted to continue further education, and 35.5% had no need for further education.Conclusion: Medical facilities need to strengthen the organization of intensive and long-term training programs, with special attention to monitoring and counseling for patients after discharge to improve the quality of care. At the same time, it is necessary to add social work graduates to departments and rooms and develop a post-discharge support system to improve the effectiveness of social work in hospitals.
Keywords: status; activities; social work; hospital